AMR-lift integration system for smart manufacturing - Ge, Keyu (Nanyang Technological University, 2024)
At the moment, industrial enterprises are in the process of transitioning to Industry 4.0. Automation is widely used in all aspects of production, which significantly improves productivity, efficiency, and quality. Automated vehicles are able to be used for raw material and product transport and flexibility to organise tasks according to the scenario. This project developed an integrated system with AMRs and lift to enable robots to move between floors and complete transport tasks with no human intervention required. This integrated system consists of three components, object detection system, automated vehicle system, and lift control system. The AMRs equipped with LiDAR will use SLAM and navigation algorithms and the lift control system will be achieved by Bluetooth.